Patterns of antibiotic use and administration in hospitalized patients in Jordan - Anan S. Jarab; Tareq L. Mukattash; Buthaina Nusairat; Mohammad Shawaqfeh; Rana Abu Farha (Elsevier, 2018)
Background: Inappropriate use of antibiotics is the leading cause of emergence of resistance. It has been estimated that two million people in the United States had infection with resistant bacteria, resulting in 23,000 deaths annually. In Jordan, more than 50% of physicians prescribe antibiotics for inappropriate indication such as common cold, and approximately 67% of adult Jordanians believe that antibiotics should be used for this purpose. It is essential to follow antibiotics prescription guidelines in order to maximize effectiveness and enhance patient safety. Objective: The study aim was to describe patterns of antibiotics prescription and adherence to guidelines of IV to oral antibiotic conversion in elderly patients visiting King Abdullah University Hospital (KAUH). Methods: A retrospective cross sectional study was conducted on hospitalized patients who were prescribed IV antibiotics. Sociodemographic and clinical data in addition to a list of IV prescribed antibiotics was collected by referring to information technology department at KAUH. Patients' eligibility for antibiotic conversion from IV to oral route was then evaluated based on Society for Healthcare Epidemiology of America criteria. Results: A total of 110 antibiotics were dispensed for 80 patients, imipenem/cilastatin was the most prescribed antibiotic (41.25%), followed by cephalosporines which were prescribed for 27.5% of the participants. Approximately half of the study patients (47.5%) were prescribed IV antibiotics despite their eligibility for oral conversion. Conclusion: This study shows a shortage in the implementation of guidelines which are important to decrease antibiotic resistance and improving clinical outcomes. The clinical Pharmacist needs to be more involved in antibiotics prescription with the aim of improving effectiveness and decreasing potential antimicrobial resistance in hospital settings. Keywords: IV antibiotics, Oral antibiotics, Clinical pharmacy, Hospitals, Jordan